46 Understanding patient and family utilisation of community-based palliative care services out-of-hours: secondary analysis of a systematic review. (14th March 2023) - Watson, Caleb; Goodrich, Joanna; Evans, Catherine; Murtagh, Fliss EM; Harding, Richard; Firth, Alice
Abstract : Background: Community-based out-of-hours services are an integral component of end-of-life care. The provision of out-of-hours services, however, is highly variable, and there is little understanding of how patients and families utilise these services. This review aims to understand and identify patterns of out-of-hours service utilisation and produce recommendations for future service design. Method: Data on service use was extracted and secondary analysis undertaken, from a systematic review of models of community out-of-hours services. In the original review, 61 papers relating to 54 studies were included. Narrative synthesis was completed, addressing four research questions on service use: 1. When do patients/families/healthcare professionals need out-of-hours services? 2.Who is contacting the out-of-hours services? 3. Is a telephone call, centre visit or home visit provided? 4. Who is providing the out-of-hours care? Results: Community-based out-of-hours palliative care services were most accessed in the evenings between 5pm and midnight, especially on weekdays (with reports of 69% of calls being made out-of-hours). Family members and carers were the most frequent contacts to the services, with studies reporting between 60% and 80% of all calls being from this group. The type of contact (telephone, centre visit or home visit) varied based on what was offered and on patient need. Over half of services were led by a single discipline (nurse). Conclusions: This secondary data analysis has illustrated out-of-hours services are highly used up to midnight, particularly by patients' family and carers. Recommendations to commissioners and service providers: Ensure telephone services are available between 5pm and midnight. Prioritise family and carers in the design of out-of-hours telephone services. Undertake further research with patients and families to understand when home visits or telephone calls are appropriate to meet patients' needs.